Comparison of Extrapyramidal Symptoms Among Outpatients With Schizophrenia on Long-Acting Injectable Antipsychotics. Issue 5 (18th September 2022) - Zhand, Naista; Labelle, Alain; Ghanem, Dana; Gujral, Preet; Han, Tommy; Huneault, Gabrielle; Jain, Gaurav Kumar; Robertson, Carrie
Abstract: Background: Extrapyramidal symptoms (EPSs) are adverse effects of antipsychotics. Different risks of EPSs have been attributed to the 3 classes of antipsychotics. This study aimed to assess EPS in a clinical sample of schizophrenia patients who are on LAI and compare the severity of EPSs among the following 3 antipsychotic groups: (1) partial agonist, (2) second-generation antipsychotics, and (3) first-generation antipsychotics. Methods: Ninety-two patients were recruited from the Schizophrenia Program Injection Clinic. Using the Extrapyramidal Symptom Rating Scale (ESRS), severity of EPS was assessed and information regarding factors associated with risk of EPS, including coprescriptions, comorbidities, and demographics, was obtained from medical charts. Group differences in ESRS scores and subscores were analyzed using 1-way analyses of variances. Results: Among the 3 groups, there was no significant difference in total ESRS scores and subscores. Risperidone was associated with higher ESRS scores when compared with paliperidone, aripiprazole, and flupenthixol. Doses above maximum were commonly used in the paliperidone group, and there was no significant difference in total ESRS scores between the low, average, or above-maximum doses of paliperidone. Conclusions: Our results demonstrated a comparative risk of EPS across all 3 antipsychotic classes. Risperidone was associated with more EPS compared with other medications. A higher threshold for the "maximum dose" of paliperidone could be considered and higher doses used with the same cautions as low-average doses.